The flexible accelerator model of investment: An application to Ugandan tea-processing firms - Twine, Edgar E.; Kiiza, B.; Bashaasha, B. (2015)
The study uses the flexible accelerator model to examine determinants of the level and growth of investment in machinery and equipment for a sample of tea-processing firms in Uganda. Using a dynamic panel data model, we find that, in the long run, the level of investment in machinery and equipment is positively influenced by the accelerator, firm-level liquidity, and a favourable investment climate in the country. Depreciation of the exchange rate negatively affects investment. We conclude that firm-level strategies that increase output and profitability, and a favourable investment policy climate, are imperative to the growth of the tea industry.